2021
DOI: 10.3390/foods10040851
|View full text |Cite
|
Sign up to set email alerts
|

A New Food Composition Database of Lactose-Free Products Commercialized in Spain: Differences in Nutritional Composition as Compared to Traditional Products

Abstract: We developed a new database to evaluate the nutritional composition of lactose-free products from Spain. The database includes dairy products and other products, all of which show the “lactose-free” declaration on their label, accounting for 327 products in total. Of these, 123 are dairy products, 16 are non-dairy products which include a dairy ingredient (5%) and 188 items (57% of the sample) are non-dairy products that do not contain any dairy ingredient. The main subgroups are yogurt (25%), milk (24%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…(2020) reported that despite the notable nutritional and label claims like ‘high protein, high calcium, and organic’ in the packages of lactose-free products, they are not effective in the purchasing behaviour of consumers. In line with that, 21% of lactose-free products do not have additional labelling claims, other than the ‘lactose-free’ claim (Martínez Rodríguez et al ., 2021). In another study, while the primary determinant in purchasing lactose-free products was the price, ‘sweeter taste’ has been a significant driver for most lactose-free consumers in the United States (Rizzo et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported that despite the notable nutritional and label claims like ‘high protein, high calcium, and organic’ in the packages of lactose-free products, they are not effective in the purchasing behaviour of consumers. In line with that, 21% of lactose-free products do not have additional labelling claims, other than the ‘lactose-free’ claim (Martínez Rodríguez et al ., 2021). In another study, while the primary determinant in purchasing lactose-free products was the price, ‘sweeter taste’ has been a significant driver for most lactose-free consumers in the United States (Rizzo et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with regulations issued by authorities, the German dairy industry offers ≤0.1% lactose content into line with EU regulations (Morlock et al, 2014). The Spanish Agency of Food Safety and Nutrition (AESAN) has issued that a product labelled lactose-free is required to contain less than 0.01% lactose (0.299 mM) (Martínez Rodríguez al., 2021). The Ministry of Agriculture and Forestry in Türkiye, has declared that lactose-free labelled milk must have a lactose content of less than 0.1% (2.99 mM) (Guide for Turkish Food Codex Notification on milk, 2019/12).…”
Section: Lactose Levelmentioning
confidence: 99%
“…In addition, gluten-free eating patterns have become a mainstream phenomenon during recent years, with perceived healthiness being the fundamental reason for this choice [21][22][23]. Moreover, consumer research shows that lactose-tolerant or undiagnosed population groups actively search for lactose-free products that they link with several potential health-related benefits [24,25].…”
Section: Introductionmentioning
confidence: 99%